Do you have any experience abroad? O gênero entrevista de emprego em cursos livres de línguas - Marzari, Gabriela Quatrin (2005)
Researches on English teachers of private language courses evolving issues related to the teaching education as well as to the teaching practice (Gervai, 1996; Chimim, 2003) and focusing on the constitution of these professionals identity have pointed out the lack of criteria explicitly defined for those teachers selection. As a consequence, unlike other teaching contexts, the teachers profile of private language courses comprises teachers distinctively qualified, being the formal education in Letras only a feature among others possible. Concerning this profile, along the study, I intend to: 1) investigate the role of the job interview while an instrument of English teachers selection at private language courses in Santa Maria, based on the interviewers conceptions on the genre; 2) identify the market equirements in relation to the English teachers profile required nowadays by the contexts investigated. Thus, I intend to demonstrate the criteria considered indispensable for the selection of a given candidate as stated by the interviewers discourse. The development of this study comes from the presupposition that, being taken as an instrument of English teachers selection, the job interview points to the real market needs, which are materialized in its participants discourse. Therefore, an analysis on the interviewers representations concerning the discourse genre job interview has allowed me to identify the topics discussed along the event, analyze the roles assumed by its participants, and define the English teachers profile usually absorbed by four private language courses in Santa Maria.